Pengaruh Perbedaan Produksi Minimum antara Alat dan Tenaga Kerja terhadap Waktu Penyelesaian, Biaya Proyek, dan Keuntungan - Angul, Aurelia Lete; Lulu, Laurensius; Bela, Krisantos Ria; Sianto, Paulus; Manubulu, Christiani Chandra; Usboko, Gregorius Paus (CV. Gio Architect, 2025)
A project is a detailed series of activities within a limited timeframe aimed at achieving specific objectives. Resources such as manpower, equipment, materials, money, and time are crucial for project success. The research objective is to determine the impact of minimum production differences between equipment and labor on project completion time, costs, and profits. The completion time for the binder course work item, based on labor and equipment, is 0.83 days, with a minimum production used of 10,000 liters. Conversely, based on equipment's minimum production, the completion time is 0.47 days, with a minimum production used of 17,500 liters. This shows a difference in completion time of 0.35 days with a reduction of 0.43%. According to the Bill of Quantities (RAB) data, the project cost is lower compared to the project cost based on labor, equipment, and labor and equipment combined. The initial profit according to the Bill of Quantities data is Rp 337,328,068.10, and the profit based on minimum labor production is Rp 145,723,835.86, resulting in a profit decrease of -56.80%.